Metabolic Syndrome and Skin Diseases - Hu, Yu; Zhu, Yun; Lian, Ni; Chen, Min; Bartke, Andrzej; Yuan, Rong (Frontiers in Endocrinology, 2019)
The increasing prevalence Metabolic syndrome (MetS) is a worldwide health problem, and the association between MetS and skin diseases has recently attracted growing attention. In this review, we summarize the associations between MetS and skin diseases, such as psoriasis, acne vulgaris, hidradenitis suppurativa, androgenetic alopecia, acanthosis nigricans, and atopic dermatitis. To discuss the potential common mechanisms underlying MetS and skin diseases, we focus on insulin signaling and insulin resistance, as well as chronic inflammation including adipokines and proinflammatory cytokines related to molecular mechanisms. A better understanding of the relationship between MetS and skin diseases contributes to early diagnosis and prevention, as well as providing clues for developing novel therapeutic strategies.